2011
DOI: 10.1007/s00415-011-6237-0
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent hypothermia with hyperhidrosis in two siblings: familial Shapiro syndrome variant

Abstract: A 21-year-old woman was referred for recurrent (up to 2 times per month) episodes of generalized hyperhidrosis and hypothermia with a core temperature fluctuating between 32 and 35°C, lasting from 2-3 h. During these attacks, the woman sweated profusely and felt faint; her skin was pale and cool and sinus bradycardia (\50 bpm) was observed. At admission, blood chemistry and cell count were unremarkable. Ictal EEGs, ECG Holter, and echocardiography were unremarkable. Brain MRI revealed the total absence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…We believe that hyperhydrosis was primarily induced by central hypogonadism in our subject since almost total remission ensued following topical testosterone therapy. This manifestation is similar to hypothalamic hypothyroidism documented in a case report [11]. It is apparent that central hypogonadism is not included as a manifestation of Shapiro Syndrome most likely because of lack of appropriate complete evaluation of hypogonadism, a well established contributor to hyperhydrosis.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We believe that hyperhydrosis was primarily induced by central hypogonadism in our subject since almost total remission ensued following topical testosterone therapy. This manifestation is similar to hypothalamic hypothyroidism documented in a case report [11]. It is apparent that central hypogonadism is not included as a manifestation of Shapiro Syndrome most likely because of lack of appropriate complete evaluation of hypogonadism, a well established contributor to hyperhydrosis.…”
Section: Discussionsupporting
confidence: 67%
“…Thermal dysregulation, especially hypothermia is postulated to result from changes in the set point of the hypothalamic thermostat, a distinct hypothalamic dysfunction attributed to probable structural abnormalities, e.g. degenerative changes, neurochemical dysfunction, inflammatory processes, other irritative mechanisms such as autoimmune disease or immunologic processes, and seizure activity etc [3] [8] [11] [15] [16]. .…”
Section: Discussionmentioning
confidence: 99%
“…Studying all cases in the literature, Tambasco et al found that only half showed CC abnormalities [2]. In addition, Belcastro et al described a familial case of SS in two siblings, where one had ACC whereas the other had a completely normal MRI, thus suggesting that callosal dysgenesis may be a marker of other molecular or microstructural abnormalities on hypothalamic networks [6]. Also of interest, acquired corpus callosum lesions have not been associated with any thermoregulatory dysfunction and do not seem to play any role in thermoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the cases with Shapiro syndrome described in the literature have not been determined hormonal abnormalities. [51617] We did not perform thyrotropin releasing hormone test cause thyroid-stimulating hormone, free thyroxine were normal.…”
Section: Discussionmentioning
confidence: 99%